The Effect of Green Packaging and Digital Payment on Consumer Behavior (A Case Study at Indomaret Asia Mega Mas Branch): Pengaruh Green Packaging dan Digital Payment terhadap Perilaku Konsumen (Studi Kasus di Indomaret Cabang Asia Mega Mas Medan) - Ryu; Dedy Lazuardi (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
The central goal of this research is to ascertain how environmentally friendly packaging (X1) and electronic payment methods (X2) influence how customers act when shopping at the Asia Mega Mas Indomaret store in Medan. The survey involved 130 participants, all of whom were customers at the Asia Mega Mas Indomaret location in Medan. The method of data collection employed direct distribution of questionnaires to respondents. The outcomes of the research demonstrate that utilizing eco-friendly packaging (X1) has a favorable impact on consumer actions (Y), and using digital payment options (X2) also positively affects consumer behavior (Y).